Porous Carbon Microparticles as Vehicles for the Intracellular Delivery of Molecules - Magno, Luis M.; Hinds, David T.; Duffy, Paul; Yadav, Rahul. B.; Ward, Andrew D.; Botchway, Stan W.; Colavita, Paula E.; Quinn, Susan J. (Frontiers in Chemistry, 2020)
IIn this study the application of porous carbon microparticles for the transport of a sparingly soluble material into cells is demonstrated. Carbon offers an intrinsically sustainable platform material that can meet the multiple and complex requirements imposed by applications in biology and medicine. Porous carbon microparticles are attractive as they are easy to handle and manipulate and combine the chemical versatility and biocompatibility of carbon with a high surface area due to their highly porous structure. The uptake of fluorescently labelled microparticles by cancer (HeLa) and normal human embryonic Kidney (HEK 293) cells was monitored by confocal fluorescence microscopy. In this way the influence of particle size, surface functionalization and the presence of transfection agent on cellular uptake were studied. In the presence of transfection agent both large (690 nm) and small microparticles (250 nm) were readily internalized by both cell lines. However, in absence of the transfection agent the uptake was influenced by particle size and surface PEGylation with the smaller nanoparticle size being delivered. The ability of microparticles to deliver a fluorescein dye model cargo was also demonstrated in normal (HEK 293) cell line. Taken together, these results indicate the potential use of these materials as candidates for biological applications.